THE GEOMETRY OF SOLAR RADIATION ENERGY EQUILIBRIUM DISTRIBUTION ON DOUBLE-PASS SOLAR AIR HEATER WITH THE ADDITION OF FIN ELEMENTS: CASE STUDY IN LIBYA - Suyitno, Budhi Muliawan; pane, erlanda augupta; Firman, La Ode Mohammad; Abuzreba, Abdelhafed; Ismail, Ismail (Journal of Applied Engineering Science, 2020)
The drying process is the most important process in the Libyan agricultural sector for agricultural products export value. Libya uses a direct drying system from solar radiation, but it provides a large energy loss and decreases the agricultural products quality. Solar air heater technology was developed to solve these problems. One indicator of the solar air heater performance is influenced by the solar radiation energy absorption distribution to heat the airflow, which can be seen from the changes in air temperature and influences the thermal efficiency. The addition of fin elements can optimize these mechanisms. This research was conducted to analyze the effect of fin elements (geometry and fin number) on air temperature rise through three methods i.e. measurement of air flow characteristics, heat transfer rate and thermal efficiency of solar air heater. The results showed that fin elements with a length of 1 m and a high range between 0.197 m to 0.221 m and the fin number of 10 pieces were able to increase the air temperature from 350C to 71.80C so that the thermal efficiency of solar air heater reached 51.5%. The performance of this technology can be applied to the agricultural products drying process in Libya.